Optimizing Co site electron structure by construction of heterogeneous interface for efficient sulfite activation on paracetamol removal - Lidong Wang; Xiuze Li; Hanxia Chen; Yifei Liang; Zhongfei Xu; Juzhe Liu; Liu, Wen; Juanjuan Qi (Journal of Environmental Chemical Engineering, 2022)
Sulfite(S(IV))-induced advanced oxidation processes (AOPs) have great prospect in the field of removing organic pollutants, yet developing highly efficient sulfite activation systems and optimizing active sites for favorable catalytic processes are important but still challenging. Herein, we have achieved a composite catalyst with modulated Co electron structure for efficient AOPs by decorating Co(OH)2 on ultrathin graphitic carbon nitride (g-C3N4) nanosheet through an adjustable strategy, which exhibits high catalytic performance in S(IV) activation system. At optimal pH 9, 92% of paracetamol (APAP) (0.005 mM) is removed with the degradation rate constant of k1 = 0.193 min−1 within 30 min in presence of the composite material. The in-situ synthesis mode introduces strong heterogeneous interface interaction, resulting in directional electron transfer from cobalt hydroxide layer to g-C3N4 sheet revealed by X-ray photoelectron spectroscopy and density functional theory (DFT) calculations. The underlying activity enhanced mechanisms for APAP in S(IV) activation system using Co(OH)2/g-C3N4 are proposed: (i) The ultrathin g-C3N4 nanosheets provide more anchoring centers for generating small Co(OH)2 nanoparticles with abundant active sites which benefit to form metastable intermediates of Co(II)-SO3; (ii) The strong interface interaction induces charge redistribution between Co(OH)2 and g-C3N4 conformed by DFT calculation, which modulates the d-band center of Co site and strengthens the bind of Co(II)-SO3, thereby giving rise to radicals (•OH, SO4• and O2•) and nonradicals (1O2 and electron transfer) oxidation for highly-efficient removal APAP. Our work will pave the way to build an environmentally friendly strategy for emerging organic pollutant degradation in water through building efficient catalysts in sulfite activation system.
Keywords: Catalytic mechanisms; Co(OH)/g-CN; d-band center; Electron structure; Sulfite activation